RMGO 2017
DOI: 10.24966/rmgo-2574/100007
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Indicators Among Women with Celiac Disease in Sudan at Ibn Sina Specialized Hospital from December 2014 to June 2015

Abstract: Celiac disease is associated with reproductive disorders, including delayed menarche, menstrual disturbances, unexplained sub fertility, and endometriosis. There is an established relationship between overt Hassan SM, et al., J Reprod Med Gynecol Obstet 2017 Background: Celiac disease is an immune-mediated mucosal disorder primarily affecting the small intestine in genetically-susceptible individuals. It may be triggered by dietary exposure to gluten. In some patients, extra-intestinal or autoimmune changes ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…29 Furthermore, menopause occurred earlier in such patients. 30 Similarly, in the study by Rujner, 11 the onset of menarche among 59 girls with CD was significantly later in untreated girls than in those on a GFD. A study by Hassan et al 30 also showed a later onset of menarche in women with CD, often after 16 years of age (64.1%).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…29 Furthermore, menopause occurred earlier in such patients. 30 Similarly, in the study by Rujner, 11 the onset of menarche among 59 girls with CD was significantly later in untreated girls than in those on a GFD. A study by Hassan et al 30 also showed a later onset of menarche in women with CD, often after 16 years of age (64.1%).…”
Section: Discussionmentioning
confidence: 82%
“…A study by Hassan et al. 30 also showed a later onset of menarche in women with CD, often after 16 years of age (64.1%).…”
Section: Discussionmentioning
confidence: 86%